2022
DOI: 10.3389/fpsyt.2022.949477
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based online intervention on mental health among undergraduate nursing students during coronavirus disease 2019 pandemic in Beijing, China: A randomized controlled trial

Abstract: ObjectiveTo evaluate the effect of mindfulness intervention on improving mental health among undergraduate nursing students during the coronavirus disease 2019 (COVID-19) pandemic in China.MethodsAn online mindfulness intervention course named Mindfulness Living With Challenge (MLWC) was developed by the research team, and a randomized controlled trial using MLWC among Chinese undergraduate nursing students was carried out. A total of 120 undergraduate nursing students were randomized into control (60 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
0
8
0
6
Order By: Relevance
“… [ 35 ] Anxiety, empathy, self-compassion Spain RCT 154 healthcare students mean age of 23 years (SD: 4.16) Mindfulness-based mobile app Instrument: The State-Trait Anxiety Inventory (STAI), The Jefferson Scale of Physician Empathy (JSPE), The Self-Compassion Scale (SCS) Significant increase in self-compassion and reducing anxiety 9. [ 36 ] Depression, anxiety, stress China RCT 120 undergraduate nursing students (mean ages 19.31 ± 0.85) Mindfulness-based online intervention Instrument: Depression-Anxiety-Stress Scale (DASS-21) Significantly reduction of anxiety and stress symptoms, as well as the improvement of mindfulness level and perceived social support 10. [ 37 ] Mental wellbeing China RCT 1255 college students (mean 32.52, SD:12.41) Internet-Based Mindfulness Training Instrument: The WHO 5-item mental wellbeing and the Mental Health Inventory Effectively improving mental health, psychological distress, life satisfaction, and sleep disturbance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 35 ] Anxiety, empathy, self-compassion Spain RCT 154 healthcare students mean age of 23 years (SD: 4.16) Mindfulness-based mobile app Instrument: The State-Trait Anxiety Inventory (STAI), The Jefferson Scale of Physician Empathy (JSPE), The Self-Compassion Scale (SCS) Significant increase in self-compassion and reducing anxiety 9. [ 36 ] Depression, anxiety, stress China RCT 120 undergraduate nursing students (mean ages 19.31 ± 0.85) Mindfulness-based online intervention Instrument: Depression-Anxiety-Stress Scale (DASS-21) Significantly reduction of anxiety and stress symptoms, as well as the improvement of mindfulness level and perceived social support 10. [ 37 ] Mental wellbeing China RCT 1255 college students (mean 32.52, SD:12.41) Internet-Based Mindfulness Training Instrument: The WHO 5-item mental wellbeing and the Mental Health Inventory Effectively improving mental health, psychological distress, life satisfaction, and sleep disturbance.…”
Section: Resultsmentioning
confidence: 99%
“…It shows that mindfulness apps are effective in reducing mental health problems in college students. 36 …”
Section: Resultsmentioning
confidence: 99%
“…Researchers have proposed a protocol aimed at implementing an online mindfulness intervention named “Mindfulness Living With Challenge” (MLWC) in COVID‐19 patients in China (Si et al., 2021 ). A randomized controlled trial has demonstrated its effect on improving the psychological well‐being of Chinese nursing students (Dai et al., 2022 ). Hence, a further randomized controlled trial can be conducted in China referring to the protocol, in order to explore the effect of MLWC on alleviating anticipated HIV stigma and depressive symptoms among HIV‐negative/unknown MSM.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars and psychiatrists have proposed a protocol on implementing a mindfulnessbased online intervention named "Mindfulness Living With Challenge" (MLWC) in COVID-19 survivors in China (Si et al, 2021). A randomized controlled trial has also demonstrated its effect on improving the psychological well-being of undergraduate nursing students in China (Dai et al, 2022). Therefore, health educators and relative agencies Furthermore, HIV-unknown MSM are among the non-testers and infrequent HIV testers, which is an important population targeted at knowledge improvement (Carey et al, 2021).…”
Section: Variablementioning
confidence: 99%